Pengaruh Pemberian Kulit Pisang Kepok Fermentasi Berbasis EM4 terhadap Performans Domba Lokal Jantan - Sonya Elisabeth Silaen; Mudastsir; Putri Damela; Qoryna Khalida; Riki Rahmatullah (Institut Agama Islam Sunan Giri Ponorogo, 2026)
The increasing cost of feed has encouraged the utilization of agricultural by-products as economical and sustainable alternative feed resources. Kepok banana (Musa paradisiaca) peel is an abundant agro-industrial by-product with considerable potential as ruminant feed; however, its utilization is constrained by its high crude fiber content. Fermentation using Effective Microorganisms-4 (EM4) is expected to improve its nutritional quality and feeding value. This study aimed to evaluate the effect of EM4-fermented kepok banana peel on the performance of local male sheep. A Completely Randomized Design (CRD) was employed with four dietary treatments and five replications. The treatments consisted of P₀ = diet containing 40% unfermented kepok banana peel, P₁ = diet containing 20% fermented kepok banana peel, P₂ = diet containing 40% fermented kepok banana peel, and P₃ = diet containing 60% fermented kepok banana peel. The observed variables included feed intake, average daily gain (ADG), feed conversion ratio (FCR), and Income Over Feed Cost (IOFC). Data were analyzed using analysis of variance (ANOVA), followed by Duncan's Multiple Range Test when significant differences were detected. The results indicated that dietary inclusion of EM4-fermented kepok banana peel had no significant effect (P>0.05) on feed intake, average daily gain, or feed conversion ratio. However, a significant effect (P<0.05) was observed on Income Over Feed Cost, with the highest value recorded in treatment P₃ (IDR 409,952 per animal). These findings demonstrate that EM4-fermented kepok banana peel can be incorporated into sheep diets at levels up to 60% without compromising productive performance while improving the economic efficiency of local male sheep production.